Application of modified clay in intensive mariculture pond: Impacts on nutrients and phytoplankton - Chi, Lianbao; Ding, Yu; He, Liyan; Wu, Zaixing; Yuan, Yongquan; Cao, Xihua; Song, Xiuxian; Yu, Zhiming (Frontiers in Marine Science, 2022)
Nutrients and phytoplankton associated with mariculture development are important concerns globally, as they can significantly impact water quality and aquaculture yield. Currently, there is still insufficient information regarding the variations in nutrients and phytoplankton community of intensive mariculture systems, and effective treatment is lacking. Here, based on consecutive daily monitoring of two Litopenaeus vannamei ponds from July to October, the dynamic variations in nutrients and phytoplankton were elucidated. In addition, modified clay (MC) method was adopted to regulate the nutrients and phytoplankton community. The temporal variations in organic and inorganic nutrients presented fluctuating upward trends. Notably, organic nutrients were the dominant species, with average proportions of TON/P in TN/P were as high as 75.29% and 87.36%, respectively. Furthermore, a marked increase in the ratios of dinoflagellates to diatoms abundance were also observed in the control pond, concurrently with dominant organic nutrients, ascending N/P ratio and decreasing Si/N and Si/P ratios. In the MC-regulated pond, MC reduced the contents of both organic and inorganic nutrients. Furthermore, a distinct change pattern of dominant phytoplankton community occurred, with green algae becoming the most abundant phytoplankton in the MC-regulated pond. This study can provide new insights into an effective treatment for managing water quality and maintaining sustainable mariculture development.